4-Methylumbelliferone as a potent and selective antitumor drug on a glioblastoma model. (29th May 2020) - Pibuel, Matías A; Díaz, Mariángeles; Molinari, Yamila; Poodts, Daniela; Silvestroff, Lucas; Lompardía, Silvina L; Franco, Paula; Hajos, Silvia E
Abstract: Glioblastoma (GBM), the most frequent primary tumor of the central nervous system, has a median survival of 14.6 months. 4-Methylumbelliferone (4MU) is a coumarin derivative widely used as a hyaluronan synthesis inhibitor with proven antitumor activity and without toxic effects reported. We aim to evaluate the antitumor effect of 4MU alone or combined with temozolomide (TMZ) on a GBM cell line, its absence of toxicity on brain cells and its selectivity for tumor cells. The antitumor effect of 4MU alone or combined with TMZ was evaluated on GL26 cells by assessing the metabolic activity through the XTT assay, cell proliferation by BrdU incorporation assay, migration by the wound healing assay, cell death by fluorescein diacetate/propidium iodide (FDA/PI) staining, apoptosis by membrane asymmetry and DNA fragmentation and metalloproteinase activity by zymography. The levels of hyaluronan and its capacity to counteract the effects of 4MU and the expression of RHAMM and CD44 were also determined. The toxicity and selectivity of 4MU were determined by XTT assay and PI staining on normal brain primary cell culture (NBPC-GFP) and GL26/NBPC-GFP cocultures. The GL26 cells expressed RHAMM but not CD44 while synthetized hyaluronan. 4MU decreased hyaluronan synthesis, diminished proliferation and induced apoptosis while reducing cell migration and the activity of metalloproteinases, which was restored by addition of hyaluronic acid. Furthermore, 4MU sensitized GL26 cells to the TMZ effect and showed selective toxicity on tumor cells without exhibiting neurotoxic effects. We demonstrated for the first time the cytotoxic effect of 4MU on GBM cells, highlighting its potential usefulness to improve GBM treatment.